Inviting bells and focus on learning (Appamāda) for students of Tri Ratna elementary school in West Jakarta - Fitriyani Fitriyani; Ayu Andriyaningsih; Wistina Seneru (International Journal of Science and Applied Science: Conference Series, 2025)
The purpose of this research is to determine the effect of inviting bells on the learning focus of Appamada students at Tri Ratna Elementary School in West Jakarta. The problems faced by the students are a lack of seriousness in attending lessons; some students are still preoccupied with their activities and do not listen to the teacher's explanations, some students like to run around during teaching and learning activities, some students arrive late to school, students feel anxious and nervous, and some students like to come in and out during learning hours. This research uses a quantitative approach, with a survey method and data processing techniques based on the results of instrument distribution. To determine the sample size in each class, proportional allocation was used, totaling 67 students from grade VI. This study was conducted at Tri Ratna Elementary School in Jakarta, with respondents from grades IV, V, and VI, academic year 2024/2025. The research results show that inviting bells have a strong and significant impact on improving learning focus. This influence indicates that the more often the inviting bells practice is conducted, the better the level of focus in learning that can be achieved. From regression analysis, it is known that inviting bells play a major role in enhancing students' learning focus, although other factors also contribute, but to a lesser extent. These results indicate that the practice of inviting bells can be a key factor in helping students become more focused in their learning, both at school and home.